Medium Optimization for Antimicrobial Production By Newly Screened Lactic Acid Bacteria - Rohmatussolihat, Rohmatussolihat; Lisdiyanti, Puspita; Yopi, Yopi; Widyastuti, Yantyati; Sukara, Endang (BRIN, 2018)
Lactic acid bacteria (LAB) are important for prevention of spoilage and pathogenic bacterial growth in foods due to their ability to generate antimicrobial substances. The objective of this study was to screen LAB for antimicrobial activity and to optimize culture medium for antimicrobial production using Response Surface Methodology (RSM) with Central Composite Design (CCD). Optimization of antimicrobial production of selected LAB was conducted with different combinations of glucose, NaCl, inoculum, and temperature. Our experimental results showed that from 129 LAB isolates, 55 showed significant inhibition against Bacillus subtilis, Escherichia coli, Micrococcus luteus, Staphylococcus aureus, Aspergillus niger, and Candida albicans. No isolates inhibited the growth of Aspergillus flavus. Lactobacillus plantarum LIPI13-2-LAB011 was selected for further study on culture medium optimization to inhibit the growth of C. albicans. From statistical analysis, the production of antimicrobial substances was significantly influenced by temperature, NaCl, and concentration of glucose. Furthermore, the optimum concentrations of glucose, concentration of inoculum, temperature, and NaCl were 1.63 %, 3.03%, 33.74°C, and 3.4%, respectively, with a maximum predicted inhibition index of 1.916, which increased 3.56-fold compared to that obtained in medium before optimization processes. The result was confirmed as when the optimum concentration of nutritions used, the inhibition index increased 3.12-fold.